Microscopic Studies of Polyaniline-poly-N-isopropylacrylamide-co-acrylic acid/ Flyash Composites Containing Dodecylbenzene Sulfonic Acid - Shashidhar; Ramprasad; Basavaraja, C.; Vishnuvardhan, T.K. (Asian Journal of Chemistry, 2012)
Polymer composites containing polyaniline-poly-N-isopropylacrylamide-co-acrylic acid (PAA)/ flyash (FA) were synthesized by chemical polymerization of aniline in an aqueous solution containing dispersed poly-N-isopropylacrylamide-co-acrylic acid (PNA)/flyash (FA) in the presence of dodecylbenzene sulfonic acid using different wt % of flyash (5, 10, 20 and 30 %). The structure and morphology of the polymer matrix affected by the added were studied by atomic force microscope. The direct current electrical conductivity was studied as a function of flyash content in the temperature range of 293-483 K. The results show an increase in conductivity values as the temperature increases at a particular concentration of flyash. However, further increase in flyash causes a decrease in the conductivity.